THE EFFECT OF USING YOUTUBE VIDEOS “LEARN ENGLISH WITH BOB THE CANADIAN” ON VOCABULARY MASTERY AT TENTH GRADE STUDENTS AT YOS SUDARSO NATIONAL HIGH SCHOOL - Tumiar Silaban; Febrina S.L Lumbantobing; Harpen H.P Silitonga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to determine the effect of using YouTube videos from the channel “Learn English with Bob the Canadian” on students’ vocabulary mastery. Vocabulary is an essential component in learning English because it supports students in developing their language skills, including listening, speaking, reading, and writing. However, many students still face difficulties in mastering vocabulary due to limited exposure and lack of engaging learning media. Therefore, the use of YouTube videos was considered as an alternative learning medium to help students improve their vocabulary mastery.This research used a quantitative approach with a pre-experimental research design. The population of this study was 63 students on tenth grade of Yos Sudarso National High School. The sample consisted of two classes, namely the experimental class 30 and the control class 30 this taken using purposive sampling.The data were collected through vocabulary tests in the form of pre-test and post-test. The data were analyzed using statistical analysis, including normality test, homogeneity test, and Independent Samples T-test.The results of the study showed that the t-test value was –0.867, while the t-table value was 2.001 at the significance level of 0.05 with the degree of freedom (df) 58. Since the t-test value was lower than the t-table value (–0.867 < 2.001) and the significance value was 0.389 which is greater than 0.05, the null hypothesis (H₀) was accepted and the alternative hypothesis (Hₐ) was rejected. This means that the use of YouTube videos “Learn English with Bob the Canadian” did not have a statistically significant effect on students’ vocabulary mastery.However, the descriptive results indicated that both classes experienced improvement in their vocabulary scores after the learning process. Therefore, YouTube videos can still be used as a supporting learning medium to make vocabulary learning more interesting and engaging for students.